Lived experiences of life with newly diagnosed advanced cancer – a qualitative interview study - Johanna Swenne; Ricko Damberg Nissen; Torben Frøstrup Hansen; Lars Henrik Jensen; Jens Søndergaard; Mette Stie (International Journal of Qualitative Studies on Health & Well-Being)
Background Incurable cancer significantly affects an individual’s life, requiering comprehensive palliative care (PC). With early PC now recommended but poorly integrated, it is essential to address patients’ experiences and concerns to ensure successful early PC integration. Aim: This study aims to investigate the experiences of life in the initial period following a diagnosis of incurable cancer to inform early PC integration. Methodology The study employed a phenomenological hermeneutical framework, drawing inspiration from interpretive descriptive methodology. Thirteen participants diagnosed with incurable cancer were purposively recruited. Data were generated through semi-structured, in-depth interviews exploring patients’ experiences of lived life, their needs and wishes. Data analysis followed an iterative process of constant comparison and thematic development. Results One main theme was identified throughout the analysis: Standing still in the storm. Three sub-themes were identified reflecting varying manifestations innhow doing so, and navigating their challenging circumstances. peace: 1) The urge to take action, 2) Clarity and awakening in the face of reality, and 3) Changed self-perception. As their understanding of their illness deepened, the patients experienced a shift towards reconciliation. Conclusion The experiences of patients living with incurable cancer reveal a complex interplay of psychological, emotional, and existential responses. It is essential that healthcare professionals address existential concerns within clinical care. By acknowledging and supporting patients’ existential struggles, discussions about sensitive topics becomes more natural and better recieved by the patients. .